Perovskite molecular sieve composite fluorescent material and preparation and application thereof
By using zeolite domain-limited growth perovskite materials in aqueous solution, combined with Al-SBA-15 molecular sieve, the problems of easy decomposition of perovskite materials under external conditions and difficulty in large-scale production are solved, and the preparation of high-efficiency fluorescent materials and the application of wide color gamut white LEDs are realized.
Patent Information
- Application Number
- CN202411882761.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
Existing perovskite luminescent materials are easy to decompose under external conditions such as oxygen, light, wet, heat, etc., which affects the luminescent efficiency. In addition, traditional synthesis methods use organic solvents and ligands, making it difficult to achieve large-scale production.
Perovskite materials are grown in situ by using the pore size limiting domain of zeolites, using only water as a solvent, avoiding the use of organic solvents and ligands, and obtaining highly efficient fluorescent materials through perovskite composite Al-SBA-15.
The efficient electrolytic catalysis and stability of perovskite materials is achieved, the fluorescence efficiency and stability are improved, the production cost is reduced, and the preparation of wide color gamut white LEDs is realized.
Smart Images

Figure CN119685014A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to a perovskite molecular sieve composite fluorescent material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] Metal halide perovskites are considered candidates for future display and lighting applications due to their advantages such as narrow spectral emission, tunable wavelength, wide color gamut, high quantum yield (PLQY) and low-cost processability. At present, perovskite light-emitting diodes (LEDs) have achieved a record peak EQE of 32.0%, and white light LEDs (WLEDs) with wide color gamut (125% for NTSC and 94% for Rec.2020) have been reported. Although perovskite LEDs have made significant progress in efficiency, the practical application of perovskite materials requires the stability of the perovskite light-emitting layer and large-scale production. The ionic structure of metal halide perovskites makes them prone to decomposition under the influence of external conditions such as oxygen, light, humidity, and heat, affecting the integrity of the crystal structure and reducing the luminous efficiency of the perovskite light-emitting layer. In addition, the traditional synthesis method of metal halide perovskite materials is difficult to achieve large-scale production due to the large use of organic solvents and a large number of organic ligand groups in the synthesis, separation and purification process, which limits its practical application in the lighting industry. Therefore, it is necessary to develop a facile and scalable strategy to produce metal halide perovskite materials with high photoluminescence and high stability. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a perovskite molecular sieve composite fluorescent material and its preparation and application. The present invention utilizes the pore size confinement of zeolite to grow perovskite materials in situ, while improving the stability of perovskite in water, increasing the contact between perovskite and reactants, increasing the exposed active sites, improving the charge transfer in the electrocatalytic process, and achieving the catalytic requirements of efficient electrolysis of water. In addition, only water is used as a solvent in the entire synthesis process, without using organic solvents and organic ligands, the synthesis temperature is low and no precious metals are used, making the synthesis process greener and less costly. The fluorescent material obtained by using perovskite composite Al-SBA-15 has a PLQY of up to 81.5%, and its stability in various environments (air, water and high temperature) is significantly improved. In addition, by encapsulating red and green perovskite phosphors with silica gel, a white perovskite LED with a wide color gamut (NTSC is 145%) is achieved, and the color coordinates are (0.333, 0.334). This ligand-free synthesis strategy provides a new method for manufacturing high-quality perovskite phosphors, and the novel perovskite molecular sieve composite material of the present invention shows faster charge transport and higher catalytic stability in oxygen evolution (OER) catalysis.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In the first aspect, the present invention provides a perovskite molecular sieve composite fluorescent material, which includes perovskite and molecular sieve, the perovskite is a CsPbBr3 cubic phase structure or a mixed phase structure of CsPb2Br5 and CsPbBr3, and the perovskite molecular sieve composite fluorescent material can emit bright green fluorescence under ultraviolet light excitation.
[0007] The emission wavelength of bright green fluorescence is 500-515nm and the excitation wavelength is 360-370nm.
[0008] In one or more embodiments, the molecular sieve includes microporous Beta (0.55-0.7nm), microporous SAPO-11 (0.44-0.67nm), microporous SAPO-34 (0.3-0.5nm), microporous ZEM-5 (0.53-0.58nm), microporous ZEM-35 (pore size 0.5-0.6nm), microporous MCM-22 (0.55-1.0nm) or mesoporous Al-SBA-15 (6-8nm), preferably mesoporous molecular sieve Al-SBA-15.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned perovskite molecular sieve composite fluorescent material, comprising the following steps:
[0010] Lead bromide, cesium bromide and molecular sieve are mixed in water, heated and stirred, and dried to obtain powder. The powder is calcined, centrifuged and dried to obtain a perovskite phosphor with bright green light, that is, a perovskite molecular sieve composite fluorescent material.
[0011] In one or more embodiments, the ratio of lead bromide, cesium bromide and molecular sieve is (0.2-0.25 mmol):(0.3-0.4 mmol):(150-200 mg).
[0012] In one or more embodiments, the lead bromide, cesium bromide and molecular sieve are mixed in water, heated and stirred, and dried to obtain powder, and the specific steps are:
[0013] Lead bromide is dissolved in water, heated and stirred until the lead bromide is completely dissolved to form a transparent aqueous solution, the lead bromide solution is filtered, added into a mixed aqueous solution of cesium bromide and molecular sieves, heated and stirred, and dried to obtain a powder.
[0014] Preferably, the heating and stirring is stirring at 60-85° C. for 0.5-2 h.
[0015] Preferably, the drying is drying at 60-90°C.
[0016] In one or more embodiments, the calcination temperature is 350-650°C, the calcination time is 0.5-2h, and the heating rate is 2-6°C / min. The perovskite molecular sieve composite fluorescent material obtained after calcination at different temperatures has different fluorescence properties. When the calcination temperature is 500-600°C, especially at 550°C, the fluorescence property is better.
[0017] In addition, the internal structure of the material is also different at different calcination temperatures. When the temperature is below 500°C, especially at 350°C-450°C, the perovskite in the perovskite molecular sieve composite fluorescent material is a mixed phase structure of CsPb2Br5 and CsPbBr3; when the temperature is above 500°C, especially at 550-650°C, the CsPb2Br5 phase disappears in the perovskite molecular sieve composite fluorescent material, and only the CsPbBr3 cubic phase structure remains.
[0018] In a third aspect, the present invention provides an application of the above-mentioned perovskite molecular sieve composite fluorescent material in the preparation of electroluminescent, photoluminescent or white light LED luminescent materials and electrochemical catalysis.
[0019] In a fourth aspect, the present invention provides a white light perovskite LED material, comprising the above-mentioned perovskite molecular sieve composite fluorescent material.
[0020] In a fifth aspect, the present invention provides a method for preparing the above-mentioned white light perovskite LED material, comprising the following steps:
[0021] The above-mentioned perovskite molecular sieve composite fluorescent material, red fluorescent powder and light-curing photoresist are mixed and heated, and the mixture is deposited on the blue LED chip for ultraviolet curing.
[0022] Preferably, the mass ratio of the perovskite molecular sieve composite fluorescent material, the red fluorescent powder and the photocurable photoresist is (5-20 mg): (1-2 mg): (100-300 mg).
[0023] Preferably, heating is performed at 30-50°C for 10-60 min.
[0024] In a sixth aspect, the present invention provides an electrocatalytic oxygen evolution device, comprising an electrolyte and a working electrode, wherein the surface of the working electrode contains the above-mentioned perovskite molecular sieve composite fluorescent material.
[0025] In the seventh aspect, the present invention provides a method for electrocatalytic oxygen evolution using perovskite molecular sieve composite fluorescent materials, comprising the following steps: loading the above-mentioned perovskite molecular sieve composite fluorescent material on a conductive substrate to prepare a working electrode and construct a three-electrode system, and performing an electrocatalytic water decomposition reaction in an alkaline electrolyte.
[0026] One or some of the above technical solutions have the following advantages or beneficial effects:
[0027] (1) The present invention provides a method for preparing an efficient and stable perovskite molecular sieve composite fluorescent material in an aqueous solution. Since the present invention utilizes the solubility of lead bromide and cesium bromide in water, the preparation process does not use high-cost, polluting organic solvents and organic ligands, and achieves the synthesis of high-efficiency luminous efficiency perovskite molecular sieve composite fluorescent materials; at the same time, since the molecular sieve used also acts as a stabilizer, the obtained perovskite molecular sieve composite fluorescent material has good stability in water, air and even at high temperatures, overcoming the shortcomings of existing perovskite fluorescent materials that rely on organic solvents and organic ligands to synthesize perovskite fluorescent materials, high costs, and easy aggregation.
[0028] (2) The perovskite molecular sieve composite fluorescent material prepared by the method of the present invention has the characteristics of high fluorescence efficiency and stability, and shows a photoluminescence quantum yield of 81.5% at 515 nm, and can be used to prepare perovskite light-emitting diodes.
[0029] (3) The perovskite molecular sieve composite fluorescent material prepared by the present invention shows a catalytic energy higher than that of commercial precious metal catalysts in the electrolytic oxygen evolution catalysis. When the composite fluorescent material is used as a catalyst in the electrocatalytic oxygen evolution, it has better catalytic power, fast charge transfer power and electrochemical catalytic stability.
[0030] (4) Different from other microporous molecular sieves (Beta, SAPO-11, SAPO-34, ZEM-5, ZEM-35 or MCM-22), the perovskite molecular sieve composite fluorescent material prepared using the mesoporous molecular sieve Al-SBA-15 has a lower overpotential when the current density is the same. Therefore, the perovskite molecular sieve composite fluorescent material prepared using the mesoporous Al-SBA-15 molecular sieve shows better catalytic performance in the catalysis of oxygen evolution in water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0032] Figure 1 XRD spectra of perovskite phosphors prepared by adding Al-SBA-15 and sintering at different temperatures in Examples 1-4 of the present invention;
[0033] Figure 2 The fluorescence spectra of the perovskite phosphors prepared by adding Al-SBA-15 and sintering at different temperatures in Examples 1-4 of the present invention;
[0034] Figure 3 This is a transmission electron microscope image (TEM) of the perovskite phosphor prepared in Example 3 of the present invention;
[0035] Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of the exterior of the perovskite phosphor prepared in Example 3 of the present invention;
[0036] Figure 5 This is a high-resolution transmission electron microscopy (HRTEM) image of the interior of the perovskite phosphor prepared in Example 3 of the present invention;
[0037] Figure 6 This is a test of the stability of the perovskite phosphor prepared in Example 3 of the present invention in air;
[0038] Figure 7 This is a test of the stability of the perovskite phosphor prepared in Example 3 of the present invention in water;
[0039] Figure 8 This is a test of the stability of the perovskite phosphor prepared in Example 3 of the present invention at high temperature;
[0040] Fig. 9 is the XRD diagram of the perovskite phosphor obtained in Comparative Example 1 of the present invention;
[0041] Fig.10 This is the electroluminescence spectrum of the white light LED described in Application Example 1 of the present invention;
[0042] Fig.11 The LSV curve of the perovskite molecular sieve composite material prepared using Al-SBA-15 molecular sieve in Application Example 2 of the present invention and the commercial noble metal catalyst RuO2;
[0043] Fig.12 LSV curves of the perovskite molecular sieve composite materials prepared using different molecular sieves in Application Example 2 of the present invention;
[0044] Fig.13 is the Tafel slope of the perovskite molecular sieve composite material and the commercial noble metal catalyst RuO2 described in Application Example 2 of the present invention;
[0045] Fig.14 The electrochemical impedance spectroscopy (EIS) of the perovskite molecular sieve composite material and the commercial noble metal catalyst RuO2 described in Application Example 2 of the present invention;
[0046] Fig.15 This is a stability test of the perovskite molecular sieve composite material for water electrolysis described in Application Example 2 of the present invention. DETAILED DESCRIPTION
[0047] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0048] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0049] The molecular sieve is Al-SBA-15 purchased from Nanjing Jicang Nanotechnology Co., Ltd.
[0050] Example 1
[0051] Preparation of perovskite phosphor by adding Al-SBA-15 molecular sieve:
[0052] 0.24mmol lead bromide was added to 20mL deionized water and stirred vigorously at 80℃ for about 30min. At the same time, 0.36mmol cesium bromide and 160mg Al-SBA-15 molecular sieve were added to 10mL deionized water and stirred for about 15min. After the lead bromide was completely dissolved to form a transparent aqueous solution, the lead bromide solution was filtered and added to the mixed solution of cesium bromide and molecular sieve, and stirred vigorously at 80℃ for 1h. The resulting solution was placed in an 80℃ oven for drying. The resulting powder was heated to 350℃ in a muffle furnace at a heating rate of 5 degrees Celsius per minute and kept heated for 30 minutes. After cooling to room temperature, water was added and centrifuged at a speed of 6000RPM / min in a centrifuge for 3 times, and the resulting mixture was dried in a vacuum drying oven at 60℃ overnight to obtain a perovskite phosphor with bright green light, that is, a perovskite molecular sieve composite fluorescent material.
[0053] Example 2
[0054] Different from Example 1, the calcination temperature is 450°C.
[0055] Example 3
[0056] Different from Example 1, the calcination temperature is 550°C.
[0057] Example 4
[0058] Different from Example 1, the calcination temperature is 650°C.
[0059] Example 5
[0060] Different from Example 3, other molecular sieves, such as Beta, SAPO-11, SAPO-34, ZEM-5, ZEM-35 or MCM-22, were used at a calcination temperature of 550°C.
[0061] Figure 1 XRD patterns of perovskite phosphors prepared by adding Al-SBA-15 and sintering at different temperatures. After adding Al-SBA-15, the CsPbBr3 luminescent phase begins to appear. When the sintering temperature is 350℃ and 450℃, it is a mixed phase of CsPb2Br5 and CsPbBr3. When the temperature reaches 550℃ and 650℃, it is a cubic phase structure of CsPbBr3.
[0062] Figure 2 The fluorescence spectra of the perovskite phosphors prepared by sintering at different temperatures with Al-SBA-15 added are shown below. Under the excitation of ultraviolet light (excitation wavelength 365nm), the highest luminescence intensity was achieved at 550℃, the emission wavelength was 515nm at the maximum luminescence intensity, and the PLQY was as high as 81.5%. This shows that the mesoporous molecular sieve Al-SBA-15 effectively confines the growth of perovskite to achieve high luminescence efficiency.
[0063] Figure 3 , Figure 4 and Figure 5 The following are transmission electron microscopy images and high-resolution transmission electron microscopy images of the prepared perovskite phosphor. Figure 4 It can be seen that the outer part of the perovskite phosphor is Al-SBA-15 with a complete void structure, and the lattice fringes with a lattice spacing of 10.1nm correspond to its (100) lattice. Figure 5 It can be seen that the interior of the perovskite phosphor is CsPbBr3, and the lattice spacing of 0.292nm corresponds to the (200) crystal plane of the cubic phase CsPbBr3. These results indicate that the perovskite nanocrystals are successfully embedded in the pores of the Al-SBA-15 molecular sieve.
[0064] Figure 6 The stability test of the prepared perovskite phosphor in air: After being stored in air (RH 60-80%) for 90 days, the luminescence intensity of the perovskite phosphor remained at 83% of the initial intensity, showing high stability in air.
[0065] Figure 7 This is a test of the stability of the prepared perovskite phosphor in water. After being immersed in water for 15 days, the luminescence intensity of the perovskite phosphor still reaches 90% of the initial luminescence intensity, showing high stability in water.
[0066] Figure 8 This is a test of the stability of the prepared perovskite phosphor at high temperature. Under the condition of heating at 80°C, the luminescence intensity of the perovskite phosphor remains at 89% of the initial value, showing high stability at high temperatures.
[0067] Comparative Example 1
[0068] Preparation of perovskite phosphor without adding Al-SBA-15 molecular sieve
[0069] Add 0.24mmol lead bromide to 20mL deionized water and stir vigorously at 80℃ for about 30min. At the same time, add 0.36mmol cesium bromide to 10mL deionized water and stir for about 15min. After the lead bromide is completely dissolved to form a transparent aqueous solution, filter the lead bromide solution and add it to the mixed solution of cesium bromide and molecular sieves, and stir vigorously at 80℃ for 1h. Finally, put the solution into an oven at 80℃ to dry. The resulting powder has no fluorescence.
[0070] Fig. 9 This is the XRD diagram of the obtained perovskite phosphor, which conforms to the phase of CsPb2Br5 and has almost no fluorescence.
[0071] Application Example 1
[0072] Preparation of white light perovskite LED
[0073] 10 mg of the perovskite phosphor prepared in Example 3, 1-2 mg of nitride red phosphor (ZYP630H), and 200 mg of optical curing adhesive (Norland-61) were mixed. In order to remove bubbles in the optical adhesive, the mixture was heated at 40°C for 0.5 hours. Finally, the mixture was deposited on a 460nm blue LED chip and cured by ultraviolet light for 50s (365nm, 80W cm -2 ).
[0074] Fig.10 is the electroluminescence spectrum of the white light LED. The CIE coordinates of the white light perovskite LED are (0.333, 0.334).
[0075] Application Example 2
[0076] Performance test of electrocatalytic oxygen evolution (OER) of perovskite molecular sieve composite materials:
[0077] The electrochemical experiments were carried out using a CHI instrument (CHI 760E) in a standard three-electrode setup, with 1 M KOH solution as the electrolyte and carbon rod and Hg / HgO electrodes (1 M KOH, 0.098 V SHE ) were used as the counter electrode and reference electrode, respectively. And the potential calibration was performed against the Hg / HgO reference electrode. No potential drift was observed after the experiment, indicating that 0.098 V relative to the standard hydrogen electrode (SHE) of the Hg / HgO reference electrode was effective in this study.
[0078] The working electrode is nickel foam (1.2 cm × 1 cm), with a thin catalyst film on the surface. It is composed of 5 mg of active material (containing about 0.5 mg of perovskite phosphor) and a few drops of Nafion (perfluorinated resin) solution (20 μL). It is then dispersed on the surface of open-pore nickel foam (NF) to form a 1 cm 2 The coating area was 1 cm × 1 cm and dried at 60 °C. Before dispersing the catalyst, the purchased NF was carefully cleaned with acetone, ultrapure water and ethanol under ultrasound assistance for 30 min to remove surface impurities. The electrolyte was degassed with high-purity oxygen (O2, 99.99%) for at least 30 min before electrochemical testing.
[0079] All potentials were calibrated to the reversible hydrogen electrode (RHE) according to the following formula:
[0080] E(RHE)=E(Hg / HgO)+0.05916×pH+0.098V#(1)
[0081] The electrochemical workstation automatically compensates 90% of the decline in each polarization curve.
[0082] Cyclic voltammetry (CV) was performed at different scan rates. -1 The linear sweep voltammetry (LSV) curve was collected at a constant rate of . The perovskite molecular sieve composite material prepared in Example 3 above, a commercial ruthenium oxide catalyst and a substrate nickel foam were subjected to a single-cycle linear sweep voltammetry (LSV) test.
[0083] Fig.11 is the LSV curve of the perovskite molecular sieve composite material and the commercial noble metal catalyst RuO2. Fig.11 It can be seen that the perovskite molecular sieve composite material only needs 355mV overpotential to reach 100mA·cm -2 The anode current density is smaller than that of the commercial precious metal catalyst RuO2 (377mV); the perovskite molecular sieve composite material only needs 277mV overpotential to reach 10mA·cm -2 The anode current density is smaller than that of the commercial noble metal catalyst RuO2 (279mV). The performance of the perovskite molecular sieve composite material is higher than that of the commercial ruthenium oxide catalytic performance and the prepared composite material does not contain noble metals, which greatly reduces the catalytic cost.
[0084] Fig.12 is the LSV curve when different molecular sieves are used in the perovskite molecular sieve composite material. The molecular sieve includes Al-SBA-15 and other molecular sieves (Beta, SAPO-11, SAPO-34, ZEM-5, ZEM-35 or MCM-22). Fig.12 It can be seen that the perovskite molecular sieve composite material synthesized using Beta molecular sieve requires an overpotential of 295mV to reach 10mA·cm -2 The anode current density of SAPO-11 molecular sieve synthesized perovskite molecular sieve composite material requires an overpotential of 351 mV to reach 10 mA cm -2 The anode current density of SAPO-34 molecular sieve synthesized perovskite molecular sieve composite material requires an overpotential of 411 mV to reach 10 mA cm -2 The anode current density of ZEM-5 molecular sieve is 10 mA cm-2. -2 The anode current density of ZEM-35 molecular sieve is 10 mA cm-2. -2 The anode current density of the perovskite molecular sieve composite material synthesized using MCM-22 molecular sieve requires an overpotential of 399mV to reach 10mA·cm -2The anode current density of 10 mA cm is 0.0447 W. The perovskite molecular sieve composite material synthesized using Al-SBA-15 molecular sieve in Example 1-4 only needs 277 mV overpotential to reach 10 mA cm -2 Obviously, the perovskite molecular sieve composite material synthesized using Al-SBA-15 molecular sieve is better than that synthesized using other molecular sieves in electrocatalysis.
[0085] Fig.13 The Tafel slope is obtained by fitting the linear part of the overpotential and current density on a logarithmic scale (log|j|). The Tafel slope of the perovskite molecular sieve composite material and the commercial noble metal catalyst RuO2 is 74.6 mV·dec lower than that of the commercial ruthenium oxide. -1 , indicating that its catalytic kinetics are faster.
[0086] Fig.14 Electrochemical impedance spectroscopy (EIS) tests were performed for different applied potentials and RHE in the frequency range of 0.01 to 100,000 Hz with an amplitude of 5 mV. The perovskite molecular sieve composite material and the commercial noble metal catalyst RuO2 were tested at an overpotential of 10 mA cm -2 The Nyquist plot of the composite material is ct The minimum value is 2.72Ω·cm 2 , illustrating the fast charge transfer kinetics during the OER process of the composite material.
[0087] Fig.15 The stability test of the perovskite molecular sieve composite material for water electrolysis is shown in Figure 1. -2 After continuous operation in 1 M KOH solution for 30 hours, the voltage stability of the composite material only increased by 0.86%, indicating that the prepared perovskite composite material has good electrochemical catalytic stability.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A perovskite molecular sieve composite fluorescent material, characterized in that: The perovskite molecular sieve composite fluorescent material comprises perovskite and molecular sieve, the perovskite is a CsPbBr3 cubic phase structure or a mixed phase structure of CsPb2Br5 and CsPbBr3, and the perovskite molecular sieve composite fluorescent material can emit bright green fluorescence under ultraviolet light excitation.
2. The perovskite molecular sieve composite fluorescent material according to claim 1, characterized in that: The emission wavelength of bright green fluorescence is 500-515nm, and the excitation wavelength is 360-370nm; Preferably, the molecular sieve is Beta, SAPO-11, SAPO-34, ZEM-5, ZEM-35, MCM-22 or Al-SBA-15, preferably Al-SBA-15; Preferably, the pore size of the Al-SBA-15 molecular sieve is 6-8 nm.
3. A method for preparing the perovskite molecular sieve composite fluorescent material according to claim 1 or 2, characterized in that: The following steps are involved: Lead bromide, cesium bromide and molecular sieve are mixed in water, heated and stirred, and dried to obtain powder. The powder is calcined, centrifuged and dried to obtain a perovskite phosphor with bright green light, that is, a perovskite molecular sieve composite fluorescent material.
4. The preparation method according to claim 3, characterized in that: The ratio of lead bromide, cesium bromide and molecular sieve is (0.2-0.25mmol):(0.3-0.4mmol):(150-200mg); The calcination temperature is 350-650°C, the calcination time is 0.5-2h, and the heating rate is 2-6°C / min.
5. The preparation method according to claim 3, characterized in that: The lead bromide, cesium bromide and molecular sieve are mixed in water, heated and stirred, and dried to obtain powder, and the specific steps are: Dissolving lead bromide in water, heating and stirring until the lead bromide is completely dissolved to form a transparent aqueous solution, filtering the lead bromide solution, adding it to a mixed aqueous solution of cesium bromide and molecular sieves, heating and stirring, and drying to obtain a powder; Preferably, the heating and stirring is stirring at 60-85° C. for 0.5-2 h; Preferably, the drying is drying at 60-90°C.
6. Use of the perovskite molecular sieve composite fluorescent material according to claim 1 or 2 or the perovskite molecular sieve composite fluorescent material obtained by the preparation method according to any one of claims 3 to 5 in the preparation of electroluminescent, photoluminescent or white light LED luminescent materials and electrochemical catalysis.
7. A white light perovskite LED material, characterized in that: It includes the perovskite molecular sieve composite fluorescent material according to claim 1 or 2.
8. A method for preparing the white light perovskite LED material according to claim 7, characterized in that: The following steps are involved: The perovskite molecular sieve composite fluorescent material, red phosphor and light-curing photoresist according to claim 1 or 2 are mixed and heated, and the mixture is deposited on a blue LED chip for ultraviolet curing; Preferably, the mass ratio of the perovskite molecular sieve composite fluorescent material, the red fluorescent powder and the light-curing photoresist is (5-20 mg): (1-2 mg): (100-300 mg); Preferably, heating is performed at 30-50°C for 10-60 min.
9. An electrocatalytic oxygen evolution device, characterized in that: It comprises an electrolyte and a working electrode, wherein the surface of the working electrode contains the perovskite molecular sieve composite fluorescent material according to claim 1 or 2.
10. A method for electrocatalytic oxygen evolution using a perovskite molecular sieve composite fluorescent material, comprising the following steps: The perovskite molecular sieve composite fluorescent material according to claim 1 or 2 is loaded on a conductive substrate to prepare a working electrode and construct a three-electrode system, and an electrocatalytic water decomposition reaction is carried out in an alkaline electrolyte.